Multiplex PCR for the detection of putative virulence factor genes mviN and vacB in Pasteurella multocida B: 2 strains - CHACHRA, DEEPTI; PARTON, ROGER; COOTE, JOHN G; JAND, S K (The Indian Journal of Animal Sciences, 2013)
Vacuolating cytotoxic activity in the mouse macrophage cell line RAW 264 was reported in Pasteurella multocida B: 2 strains associated with haemorrhagic septicaemia in buffaloes and cattle. A putative virulence-related gene mviN was reported in the sequenced genome of P. multocida serotype A (avian strain Pm70). MviN is an integral membrane protein that belongs to MATE (multi-antimicrobial extrusion) family. The present study was undertaken to detect the presence of putative virulence- related genes, viz. vacB and mviN among P. multocida B: 2 strains (8). Sequence information for the vacB gene was obtained from the sequenced genome of P. multocida serotype A (avian strain Pm70). Oligonucleotide primers were designed for these genes and synthesized. All the 8 P. multocida B: 2 strains, 1 P. multocida type A 3 (bovine) and 1 P. multocida type D (pig) strain had both of these genes of the expected size (1.5 Kb for mviN and 2.4 Kb for vacB) as confirmed by PCR. E. coli K12 used as negative control did not show any band. Both these putative virulence-related genes were amplified in a single reaction mixture using multiplex PCR. The expected size (1.5 Kb for mviN and 2.4 Kb for vacB) of both the genes was obtained. This is the first report of the detection of these virulence-related genes among P. multocida B: 2 strains. Besides providing additional targets for diagnostic applications, the identification and subsequent analysis of virulence-related genes in P. multocida B: 2 strains may help in improving our understanding of molecular mechanism of adaptation, survival and virulence of P. multocida B: 2